Damping analysis of a transversely isotropic piezothermoelastic nanobeam resonator based on the MGT thermoelasticity - Srivastava A.; Mukhopadhyay S. (My University, 2025)
The present work investigates the vibration of a piezothermoelastic nanobeam in the frame of Moore–Gibson–Thompson (MGT) thermoelasticity theory. Closed form analytical expressions for the thermoelastic damping in terms of quality factor and frequency shift for a homogeneous transversely isotropic piezothermoelastic (PTE) beam is derived by using Euler–Bernoulli beam theory and complex frequency approach. Detailed analysis of damping of vibration owing to thermal fluctuations and electric potential in the present context under three sets of boundary conditions is attempted to investigate the influence of modes of vibration, electric potential, and beam length on energy dissipation caused by thermoelastic damping in PTE beam resonators. Analytical results are illustrated with the help of graphical plots on numerical findings in the case of the nanobeam resonator of Lead Zirconate Titanate (PZT-5A) material. The investigation brings out some significant key findings and observations in view of MGT heat conduction model. © 2024 Elsevier Masson SAS